2013
DOI: 10.1016/j.preteyeres.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Herpes keratitis

Abstract: Herpes Simplex Virus-1 (HSV-1) infects the majority of the world’s population. These infections are often asymptomatic, but ocular HSV-1 infections cause multiple pathologies with perhaps the most destructive being Herpes Stromal Keratitis (HSK). HSK lesions, which are immunoinflammatory in nature, can recur throughout life and often cause progressive corneal scaring resulting in visual impairment. Current treatment involves broad local immunosuppression with topical steroids along with antiviral coverage. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
258
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(264 citation statements)
references
References 198 publications
3
258
0
3
Order By: Relevance
“…We identified 122 novel O-glycosylation sites on 28 HCMV proteins, including gB, gH, gL, gN, and gO (Table 2 and supplemental Data Sets S1 and S4). Most of the identified glycoproteins had a relatively small number of sites (1)(2)(3)(4)(5)(6)(7)(8), with the exception of RL12 and UL22A, in which we found 18 and 14 sites, respectively. Five HCMV envelope glycoproteins are indispensable for replication: gB, gH, gL, gM, and gN (57).…”
Section: Mapping O-glycosites In Human Herpesvirusesmentioning
confidence: 56%
“…We identified 122 novel O-glycosylation sites on 28 HCMV proteins, including gB, gH, gL, gN, and gO (Table 2 and supplemental Data Sets S1 and S4). Most of the identified glycoproteins had a relatively small number of sites (1)(2)(3)(4)(5)(6)(7)(8), with the exception of RL12 and UL22A, in which we found 18 and 14 sites, respectively. Five HCMV envelope glycoproteins are indispensable for replication: gB, gH, gL, gM, and gN (57).…”
Section: Mapping O-glycosites In Human Herpesvirusesmentioning
confidence: 56%
“…13,31 Previously, we reported that HSV-1 causes regression of sensory fibers innervating the cornea and loss of their function during the acute phase of infection, followed by abnormal nerve regeneration at a time point consistent with establishment of viral latency. 23 Since 8 days pi, the time point pi of maximal observed loss of innervation, coincides with a highly inflammatory milieu in the infected cornea, 12,14 we hypothesized the mechanism triggering regression of corneal nerves is immune system mediated. To test this hypothesis, we evaluated the effects of DEX, a clinically prescribed, anti-inflammatory reagent, 25,26 on the corneal nerve network after HSV-1 infection.…”
Section: Dex Prevents Corneal Nerve Regression and Sensation Loss Aftmentioning
confidence: 99%
“…tory cytokines and chemokines that result in the recruitment of neutrophils and then various types of T cells into the cornea (21)(22)(23)(24). For some infections, like HSV infections, blood vessels and lymphatics infiltrate into the cornea, amplifying the response.…”
Section: Fig 9 Flow Cytometry Analysis Of T-cell Subsets In Infectedmentioning
confidence: 99%